SEVEN SAGES OF GREECE: BETWEEN DEMOCRACY AND TYRANNY - Turenko (Туренко Віталій Едуардович), Vitalii; Oliinyk (Олійник Артем Юрійович), Artem (Politology bulletin, 2021)
In the study, in the context of the theme of the seven sages of Greece, the corpus of factual material was analyzed, followed by the use of general scientific and specific methods, and the author’s conclusions were obtained, including those of a misdirected nature.The thesis is substantiated that philosophy arises not only as a departure from mythological perception, but also as an activity-based reflection on socio-political reality in a particular polis. Accordingly, despite the fact that the sages perceived philosophy only as a reflection on nature, but as a study of the surrounding world and, on the basis of this, an attempt to make this or that political reality stable and loyal to all residents of a particular polis.Based on previous scientific works at the intersection of philosophy, political science, history, linguistics and semantics, the context of the use of a number of important concepts is clarified, regardless of further connotational loads, which has transformed meanings from time to time. Accordingly, the main focus of the article focuses on the dichotomous division of the seven wise men into parties: democrats and tyrants.Since the attitude towards tyrants and the phenomenon of tyranny is more or less positionally expressed in the philosophical tradition since Plato, the main issue was precisely in the temporal segment of the «pre-Platonic», pre-classical, and then it was complicated by numerous factors. Among them, in addition to the limited primary sources, there is a difference in the interpretation of ancient allegories, the imposition of a modern understanding of socio-political processes on the socio-economic conditionality of the inhabitants of the policies more than 2.5 thousand years ago, and the like. This creates a challenge for comprehending a full-fledged political picture of life or Ionia, or continental Hellas.Based on specific and comprehensive data, for example, the duties and powers of certain state officials of the archaic era, it was possible to theorize and find their confirmation / refutation in works of a later period. This constituted an important part of the study, as the aim is to provide an unbiased analysis of both parties and their supporters, regardless of the moral and ethical side. The main thing here is the clarification of the role, place, importance and popularity of both approaches to the 404 event in Athens, which qualitatively changed public discourse in a decisive way, completely moving away in black and white tones.

У дослідженні в контексті теми семи мудреців було проаналізовано корпус фактологічного матеріалу і з подальшим використанням загальнонаукових та специфічних методів та одержано авторські висновки, в тому числі й міждисплінарного характеру.Обгрунтовується теза, що філософія виникає не лише як відхід від міфологічного сприйняття, але й як діяльнісна рефлексія щодо соціально-політичної реальності в тому чи іншому полісі. Відповідно, зважаючи на те, що мудреці сприймали філософію не (с)тільки як мaркування про природу, а як розвідування навколишнього світу і на основі цього намагання зробити ту чи іншу політичну дійсність стабільною і лояльною до усіх жителів конкретного поліса.Спираючись на попередні розвідки на перетині філософії, політології, історії, лінгвістики та семантики, з’ясовується контекст вживання ряду важливих понять безвідносно до подальших конотаційних навантажень, що трансформувало сенси від часу до часу. Відповідно, основна увага статті зосереджується на виокремленій проблематиці правителів-мудреців та їх дихотомічного поділу на партії: демократи і тирани.Оскільки ставлення до тиранів і феномену тиранії більш-менш позиційно виражено у філософській традиції починаючи з Платона, то головне питання перебувало саме у темпоральному відрізку «доплатонівському», докласичному, а відтак і було ускладнено численими факторами. Серед них, окрім обмеженості першоджерел, є відмінне тлумачення античних алегорій, накладання сучасного розуміння суспільно-політичних процесів та соціально-економічної обумовленості жителів полісів понад 2,5 тисячі років тому тощо. Це і створює виклик для осягнення повноцінної політичної картини життя чи то Іонії, чи континентальної Еллади.Спираючись на конкретні та вичерпні дані, до прикладу, обов’язків і повноважень тих чи інших державних посадовців архаїчної доби, вдалося теоретизувати і віднаходити їх підтвердження/спростування у роботах більш пізнього періоду. Це склало важливу частину дослідження, оскільки метою є незаангажований аналіз обох партій та їх прихильників, незалежно від морально-етичного боку. Головним тут проявляється з’ясування ролі, місця, важливості та популярності обох підходів до події 404 року в Афінах, яка якісно змінила суспільний дискурс вирішальним чином, цілком відійшовши у чорно-білі тона.
СІМ МУДРЕЦІВ АНТИЧНОСТІ: МІЖ ТИРАНІЄЮ І ДЕМОКРАТІЄЮ
Keywords: early Greek philosophy; seven sages of Greece; tyranny; democracy; politics; law; рання грецька філософія; «сім мудреців»; тиранія; демократія; політика; право